2021
DOI: 10.1111/bjet.13114
|View full text |Cite
|
Sign up to set email alerts
|

Learning with technology during emergencies: A systematic review of K‐12 education

Abstract: Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID‐19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 34 publications
1
63
1
6
Order By: Relevance
“…during an emergency or crisis" [4] (pp. [1][2][3][4][5][6][7][8][9][10][11][12][13], it addresses problems primarily concerning the general teaching and learning levels and puts content and subject-related problems in the background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…during an emergency or crisis" [4] (pp. [1][2][3][4][5][6][7][8][9][10][11][12][13], it addresses problems primarily concerning the general teaching and learning levels and puts content and subject-related problems in the background.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by "a temporary shift of instructional delivery to an alternate delivery mode due to crisis circumstances" [4] (pp. [1][2][3][4][5][6][7][8][9][10][11][12][13], i.e., to quickly set up temporary solutions for maintaining and enabling teaching despite spatial distance. Due to the urgency of shifting lessons to an online format, the term "panic-gogy" is also used to describe the situation both teachers and learners found themselves in during the spring of 2020 [9,10].…”
Section: Introduction 1emergency Remote Teaching In Germany and Spainmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reported that pandemic school closures affected 94% of the world's student population [86] according to UNESCO, the greatest percentage of students impacted by these closures was 82.8%, occurring 30 March 2020 [87]. After declaration of the pandemic, mid-March 2020, in-class meetings were no longer permitted for learners and schooling proceeded online.…”
Section: Extending the Self-videoconferencing In Public Spacementioning
confidence: 99%
“…Social distancing, face masks wearing in public places and stay-at-home measures were recommended, to "flatten the curve" and slow the spread of COVID-19. Reportedly, the pandemic affected 94% of the world's student population, educational institutions struggling to diminish the impact of the crisis [7]. Buildings were untouched, the population was not displaced, but traditional educational face-to-face interactions were put on hold for an indefinite period.…”
Section: Introductionmentioning
confidence: 99%